Interweaving Between Genetic and Epigenetic Studies on Childhood Asthma - Aniruddha Rathod (Epigenetics Insights, 2020)
The cause and underlying mechanisms that contribute to asthma pathogenesis are not well known. Both genome- and epigenome-wide association studies have identified genes associated with asthma risk. It is unknown to what extent genes identified in these two types of studies overlap. Based on existing literature and the DisGeNET database, we extracted overlapping genes identified in genetic and epigenetic studies of childhood asthma. Through analyses of variance, we assessed whether DNA methylation (DNAm) at 5′-C-phosphate-G-3′ (CpGs) on the overlapping genes was associated with neighboring single-nucleotide polymorphisms (SNPs) within 1M base pairs (bps) and with low linkage disequilibrium ( r 2   <  0.2) in the childhood asthma-related genes. In total, 285 genes from genetic studies and 226 genes from epigenetic studies were shown to be associated with asthma risk, of which six overlap. Of the six genes, 79 CpGs and 8229 unique neighboring SNPs (1M bps) were included in methylation quantitative loci (methQTL) assessment analyses. We tested the association of DNAm at each of the 79 CpG sites with its neighboring SNPs. After adjusting for multiple testing by controlling the false discovery rate to 0.05 when testing methQTL for each CpG site, we found statistically significant associations in three genes with their neighboring SNPs and identified 34 unique methQTLs. The rather limited overlap in genes between genetic and epigenetic studies on asthma and the absence of methQTL in some of the overlapping genes highlight a need to jointly, rather than independently, examine genetic and epigenetic effects on asthma risk to improve our understanding of the underlying mechanisms of asthma.